The Usefulness of Procalcitonin in the Diagnosis of Appendicitis in Children: A Pilot Study - Khan, Abu N. G. A.; Sawan, Abdel; Likourezos, Antonios; Schnellinger, Mark; Garcia, Estavan (Emergency Medicine International, 2012)
Objective. To assess the predictive value of procalcitonin in detecting acute appendicitis (AP) in children, and to determine a cutoff value of procalcitonin which can safely include/exclude the diagnosis of acute appendicitis in children with acute abdominal pain. Methods. Prospective cohort study of children aged 5–17 years presenting to the emergency room with right lower quadrant (RLQ) tenderness and strong suspicion for acute AP. In addition to standard diagnostic workup for acute AP, a quantitative procalcitonin level was measured using immunoluminometric assay. Recursive partitioning model was used to assess the usefulness of procalcitonin in the diagnosis of appendicitis. Results. Of the 50 children studied, 48% were diagnosed to have AP. The mean procalcitonin level was higher among the children with appendicitis (P=0.3). Using the recursive partitioning model, we identified a cutoff value of procalcitonin level of 0.39 with a likelihood ratio presence of appendicitis 3.25 and absence of appendicitis 0.8. None of the study subjects with procalcitonin level <0.39 and WBC count of <6.76 K had appendicitis. Conclusions. In conjunction with the clinical symptoms, a procalcitonin level and WBC count could be a strong predictor of acute appendicitis in children.